Potential of Lignin-Rich Grass, Pennisetum purpureum × Pennisetum typhoideum, as a Feedstock for Biogas Production - Panchanit Pardang (2020)
© 2020 American Society of Civil Engineers. Effects of harvesting ages (45, 70, and 90 days), pretreatments (fresh and silage), and temperatures (35°C and 55°C) on biogas production from P. purpureum × P. typhoideum (giant juncao grass, GJG) were investigated. The biochemical methane potential test was used to determine specific methane yields, and results were simulated using the modified Gompertz model. GJGs at younger harvesting ages gave higher specific methane yields, partly due to their lower lignin content. Ensiled GJGs tended to offer superior degradation performance to fresh grass under mesophilic conditions. However, under thermophilic conditions, similar specific methane yields were obtained, suggesting that effects of high temperature digestion prevailed over ensiling process advantages. Higher specific methane yields were attained under thermophilic conditions for GJGs having the same harvesting age and pretreatment. Owing to its high mass yield, the fresh 90-day GJG was recommended as the feedstock for biogas production under thermophilic conditions. Methane yield up to 10,356 m3 CH4 ha-1 year-1 was provided from this grass, which was 1.6-90.1 times higher than that estimated from other biomass types investigated.